Practice day may be unnecessary prior to testing knee extensor strength in young healthy adults. Issue 1 (1st January 2020) - Hibbert, Jamie E.; Kulas, Anthony S.; Rider, Patrick M.; Domire, Zachary J.
ABSTRACT: A practice session is common prior to strength testing. However, the benefits of practice have not been previously reported. The purpose of this study was to determine the effect of a practice session on peak torque, mean torque and between trial variability across three test days. We hypothesized that peak and mean torque would be higher and less variable the second and third test days than the first. Twenty-five healthy, young participants completed 3 maximal voluntary isometric and isokinetic knee extensions on three separate days. No difference in isometric torque was found between days 1 and 2, but there was a significant decrease in isokinetic torque (8.45 Nm). There was a significant decrease in both mean isometric and isokinetic torque from day 1 to day 3 (12.67 and 13.59 Nm). Contrary to our hypothesis, no benefit from a practice session was found. Healthy, young adults are able to produce peak knee extensor torques on the first day of testing and do not demonstrate any benefit from additional testing. Thus, a practice day preceding isometric and isokinetic knee extensor strength testing may not be necessary when testing healthy, young participants, and may, in fact, negatively impact subsequent strength measurements.